2013
DOI: 10.1289/ehp.1306638
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on the Use of Alternative Species in Human Health and Ecological Hazard Assessments

Abstract: Background: Traditional animal toxicity tests can be time and resource intensive, thereby limiting the number of chemicals that can be comprehensively tested for potential hazards to humans and/or to the environment.Objective: We compared several types of data to demonstrate how alternative models can be used to inform both human and ecological risk assessment.Methods: We reviewed and compared data derived from high throughput in vitro assays to fish reproductive tests for seven chemicals. We investigated whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 97 publications
(106 reference statements)
0
84
0
Order By: Relevance
“…Due to similarities in molecular mechanisms that lead to toxicological outcomes, AOPs also provide a defensible framework for extrapolating chemical effects across species, thus allowing a broader integration of all available information and generation of robust hypotheses to be tested (Perkins et al, 2013). For example, in the case of pharmaceutical micropollutants, the existing knowledge on their actions in mammals can be used to develop AOPs (Brausch et al, 2012), which along with evaluation of molecular targets conservation could help in predicting relevant toxicity outcomes in other species of concern, such as fish (Gunnarsson et al, 2008;Domingo et al, 2010).…”
Section: Development Of Chronic Toxicity Aops: Information-rich Situamentioning
confidence: 99%
See 1 more Smart Citation
“…Due to similarities in molecular mechanisms that lead to toxicological outcomes, AOPs also provide a defensible framework for extrapolating chemical effects across species, thus allowing a broader integration of all available information and generation of robust hypotheses to be tested (Perkins et al, 2013). For example, in the case of pharmaceutical micropollutants, the existing knowledge on their actions in mammals can be used to develop AOPs (Brausch et al, 2012), which along with evaluation of molecular targets conservation could help in predicting relevant toxicity outcomes in other species of concern, such as fish (Gunnarsson et al, 2008;Domingo et al, 2010).…”
Section: Development Of Chronic Toxicity Aops: Information-rich Situamentioning
confidence: 99%
“…The usefulness of the AOP framework for cross-species extrapolations has been highlighted previously (Celander et al, 2011;Perkins et al, 2013) and several examples of how toxicokinetic and toxicodynamic processes contribute to differences in species sensitivity have been given above. Below, we will briefly discuss how AOPs can be used to support common strategies applied for species extrapolation (Section 4.1) and present a venue for a broader integration of evolutionary life history theory with AOP concept, which could be developed into another useful approach to cross-species extrapolation (Section 4.2).…”
Section: Aop-based Extrapolation Across Speciesmentioning
confidence: 99%
“…From the same study, US EPA (2009a,b) derived a TDI of 80 ng kg À1 bw, accounting for an extrapolation factor based on the toxicokinetics differences in humans, and animals. It seems worthy to note that the above modeled TDIs might need re-assessment on the evidences of other toxicological end-points such as sperm quality (Joensen et al, 2009) or delayed pregnancy (Fei et al, 2009) having been observed in the average population being exposed to considerable lower level than the TDI and within a combined exposure assessment, also targeted on the identification of Adverse Outcome Pathways via alternative methods based on high throughput screening tests (Perkins et al, 2013).…”
Section: Risk Characterizationmentioning
confidence: 99%
“…The steroidogenic pathway is well conserved among species (Perkins et al, 2013) allowing for extrapolation of results across vertebrate classes and to other steroid-producing organisms.…”
Section: Introductionmentioning
confidence: 99%